Reduced platelet mitochondrial respiration and oxidative phosphorylation in patients with post COVID-19 syndrome are regenerated after spa rehabilitation and targeted ubiquinol therapy - Sumbalová, Zuzana; Kucharská, Jarmila; Rausová, Zuzana; Palacka, Patrik; Kovalčíková, Eleonóra; Takácsová, Timea; Mojto, Viliam; Navas, Plácido; Lopéz-Lluch, Guillermo; Gvozdjáková, Anna (Frontiers in Molecular Biosciences, 2022)
European Association of Spa Rehabilitation recommend spa rehabilitation for patients with post COVID-19 syndrome (post C-19). We studied effects of special mountain spa rehabilitation program and its combination with ubiquinol (reduced form of coenzyme Q10 – CoQ10) supplementation on pulmonary function, clinical symptoms, endogenous CoQ10 levels, and platelet mitochondrial bioenergetics of patients with post C-19. 36 patients with post C-19 enrolled for rehabilitation in mountain spa resort and 15 healthy volunteers representing the control group were included in this study. 14 patients with post C-19 (MR group) were on mountain spa rehabilitation lasting 16 – 18 days, 22 patients (MRQ group) were supplemented with ubiquinol (2x100 mg/day) during the rehabilitation and additional 12–14 days at home. Clinical symptoms and functional capacity of the lungs were determined in patients before and after the spa rehabilitation program. Platelet bioenergetics by high-resolution respirometry, plasma TBARS concentration, and CoQ10 concentration in blood, plasma and platelets were evaluated before and after the spa rehabilitation program, and in 8 patients of MRQ group also after additional 12–14 days of CoQ10 supplementation. Pulmonary function and clinical symptoms improved after the rehabilitation program in both groups, 48.2 % of symptoms disappeared in the MR group and 62.8 % in the MRQ group. Platelet mitochondrial Complex I (CI)-linked oxidative phosphorylation (OXPHOS) and electron transfer (ET) capacity were markedly reduced in both groups of patients. After the rehabilitation program the improvement of these parameters was significant in the MRQ group and moderate in the MR group. CI-linked OXPHOS and ET capacity increased further after additional 12–14 days of CoQ10 supplementation. CoQ10 concentration in platelets, blood and plasma markedly raised after the spa rehabilitation with ubiquinol supplementation, not in non-supplemented group. In the MRQ group all parameters of platelet mitochondrial respiration correlated with CoQ10 concentration in platelets, and the increase in CI-linked OXPHOS and ET capacity correlated with the increase of CoQ10 concentration in platelets. Our data show a significant role of supplemented ubiquinol in accelerationg the recovery of mitochondrial health in patients with post C-19. Mountain spa rehabilitation with coenzyme Q10 supplementation could be recommended to patients with post C-19.